Third places and educational justice: public libraries in the context of COVID-19 - Thiele, Katja; Klagge, Britta (ERDKUNDE, 2021)
Public libraries play an important role in supporting and safeguarding educational justice and societal participation. The so-called third place – with the home as the first place and the school or workplace as the second place – forms a central support structure beyond formal educational institutions. The corona crisis forced public libraries to close temporarily, adapt their services, and develop new formats. This article analyzes these latest developments in Germany and Europe, illustrating the challenges public libraries are facing as a result of the corona crisis. The main research focus is on public libraries’ recent transformation – not only during the corona crisis – and its implications for safeguarding educational justice. This study will discuss the challenges posed by these developments based on the case of the German city of Bonn, thereby illustrating the importance of public libraries’ geography in strengthening educational justice.